Improving Student Learning Outcomes in the Human Digestive System through the Application of Problem-Based Learning Model - Tetii Apriati; Masra Latjompoh; Zhi-Guo Xiao (Classroom Experiences, 2025)
Learning is a process of interaction between learning resources between students and teachers in a learning environment. The application of the Problem Based Learning method can be a solution for teachers to improve student learning outcomes. This study focuses on the impact of the Problem-Based Learning (PBL) model on student learning outcomes in the topic of the digestive system in Class Mathematics and Natural Sciences (MIA) 2 at State High School (SMAN) 9 Mataram. The research involved 33 students from Class XI MIA 2 at SMAN 9 Mataram, and the learning improvement actions were implemented over three cycles. The study aimed to explore the effectiveness of the PBL method in enhancing student learning achievements, expanding teachers' professional perspectives, and contributing to innovative teaching strategies within the institution. The findings indicate a significant improvement in student learning outcomes, as reflected in the evaluation scores: 35% of students (7 students) achieved scores above the minimum completion criteria in the pre-cycle, 50% (10 students) in Cycle 1, and 85% (17 students) in Cycle 2. This study demonstrates that the application of the PBL model has a positive impact on student learning achievements in Biology, specifically in the digestive system topic.